GIS-Based 'Banua Siaga' Platform for Enhancing Disaster Preparedness Through Health Post Mapping in Palu - Budiman Budiman; Ahmad Yani; Fatmawati Fatmawati (Journal of Public Health and Pharmacy)
Introduction: Household safety and disaster evacuation are crucial global issues, especially in Southeast Asia, where Indonesia is highly vulnerable to natural disasters. Palu City, Central Sulawesi, frequently experiences disasters such as earthquakes, tsunamis, and landslides, necessitating effective disaster management strategies. The increasing escalation and intensity of disasters demand improved preparedness and response mechanisms. This study aims to develop an interactive platform utilizing Geographic Information System (GIS) technology to map health service posts and evacuation points in Palu City, ensuring real-time access to crucial disaster response information.